Perioperative management in acute and chronic spinal cord injury, narrative review - Israel Valdez-Resendiz; Estefany Nohemí Salgado-Camarillo; Fernanda Hernández-Morales; César Alejandro Martínez-de los Santos; Chiara Robba (Journal of Anesthesia, Analgesia and Critical Care, 2025)
Abstract Spinal cord injury (SCI) causes temporary or permanent changes and alterations in patients’ motor, sensory, or autonomic function, significantly impacting their quality of life and requiring clear goals and optimization of anesthesia and perioperative care for acute and chronic spinal cord injuries. SCI results from various etiologies and involving two principal pathophysiological mechanisms: primary and secondary injury. The first is result of the traumatic event, with irreversible neuronal damage, the second is generated as a consequence and in the minutes after the first and can continue for weeks or months causing degenerative damage to the spinal cord. It is in the secondary lesion where the objectives of anesthetic and perioperative management should be focused, especially in acute lesion. A conscientious and detailed preoperative evaluation allows to identify, injury level, evolution time, airway evaluation, cervical stability, hemodynamic status, ventilatory function and associated injuries must be determined. It is important to differentiate potential hemodynamic alterations and types of shock to prevent, especially in injuries greater than T6 and if necessary, provide early management in order to maintain adequate spinal cord perfusion. The objective of this review is to identify the pathophysiological mechanisms of spinal cord injury and the secondary systemic alterations and complications, as well as to establish specific optimization objectives during anesthetic management and perioperative care, which could reduce injury progression, prevent and control potential complications, and improve the quality of life of patients with this condition.